Emergent Supersymmetry in Warped Backgrounds - Nagasawa, T.; Ohya, S.; Sakamoto, K.; Sakamoto, M. (Symmetry, Integrability and Geometry: Methods and Applications, 2011)
We show that quantum mechanical supersymmetries are emerged in Kaluza-Klein spectrum of linearized gravity in several warped backgrounds as a consequence of higher-dimensional general coordinate invariance. These emergent supersymmetries play an essential role for the spectral structure of braneworld gravity. We show that for the case of braneworld models with two codimension-1 branes the spectral pattern is completely determined only through the supersymmetries.